DESAIN E-LKPD BERBASIS PROBLEM BASED LEARNING TERINTEGRASI ETNOSAINS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PEMBELAJARAN IPAS FASE C - Susandra, Ratih Rintan (Universitas Tanjungpura, 2025)
IPAS learning in elementary schools often lacks contextual and engaging approaches, leading to low critical thinking skills. This study aims to develop an interactive E-LKPD based on Problem Based Learning (PBL) integrated with ethnoscience to improve students